Effects of Microplastics on Selected Earthworm Species - Marek Klimasz; Anna Grobelak (Toxics)
Microplastics currently pose a serious threat to aquatic and terrestrial ecosystems. The high mobility of particles and their diversity in size, material and shape lets them spread widely. Further complicating matters is the ever-expanding plastics industry and modifications to its manufacturing processes. To date, many cases of negative, often toxic effects of microplastics on various species such as fish, birds and mammals have been documented. The methodology for measuring and determining the effects of microplastics on soil organisms is still an area of little understanding and certainly requires further study. In our conducted experiment, we reported the effects of selected microplastics in soil (polyethylene, polyethylene terephthalate, polystyrene, polyamide and a mixture of these plastics) at concentrations of 0.1% w/v and 1% w/v at two time intervals, one and three months, on five different earthworm species, identifying the species-related microplastic response. This study investigated the effects of different microplastics on biological parameters such as survival and respiration and biochemical parameters such as effects on glutathione s-transferase (GST), a marker of detoxification and adaptive response in earthworm species Eisenia andrei, Eisenia fetida, Lumbricus terrestris, Apporectoda caliginosa and Dendrobena veneta. The choices of species and the types of microplastic selected are intended to map the occurrence of microplastic contamination in the soil and determine the adaptation of earthworms to changing environmental conditions, considering their ecological significance and functional diversity in soil ecosystems.